Sarea cirrhendocarpa, a fungus species new to science from the southern Rocky Mountains - Raynor, Seth J.; Watts, Jacob L.; Manzitto-Tripp, Erin A. (Phytotaxa, 2024)
Sarea cirrhendocarpa, a resinicolous fungus, is here described as new to science from two specimens collected in the Indian Peaks Wilderness (Arapaho-Roosevelt National Forest, Colorado, USA) during the summer of 2023, a third specimen from Holy Cross Wilderness (White River National Forest, Colorado, USA) during the summer of 2024, and a fourth specimen from the Kachina Peaks Wilderness (Coconino National Forest, Arizona, USA) that was collected in 1998. The new species is readily distinguished from its closest relative, Sarea resinae, by its larger apothecia, smaller asci, smaller ascospores, and burnt orange hymenium (bicolored towards uppermost portions) among other traits. A phylogeny derived from the nuclear ribosomal internal transcribed spacer (ITS) region suggests that S. cirrhendocarpa is sister to and genetically distinct specimens of Sarea resinae sampled from around the world including North America. These molecular results in combination with the clear morphological differences lead us to propose this as a new species so far only known from the southern Rocky Mountains of North America. This new taxon is placed for the time being within the genus Sarea owing to inconclusive phylogenetic and morphological evidence that would support generic separation within the Sareomycetes. The name Sarea resinae is retained and new combinations for S. klamathica and S. lignicola are provided.